Upaya Meningkatkan Pemahaman Peserta Didik Terhadap Mata Pelajaran Ski Kelas 5 Melalui Metode Edutainment Di Mi Dipanegara Ranterejo Klirong Kebumen - Abdillah, Faizal; Latifah, Nurul; Fatimah, Siti; Kurniawan, Benny (IAINU Kebumen, 2022)
This research is motivated by the low understanding of students in the SKI subject matter of Khulafaur Rashidin Uthman bin Affan. From this problem, the researcher provides a solution by applying the edutainment learning method, which is a learning method by means of learning that is designed in such a way, so that the content of education and entertainment can be combined. The method in this research is classroom action research which is a research model that consists of four stages starting from planning, action, observation, and reflection. In this classroom action research, the researcher refers to the research scheme proposed by Kemmis and Tegart. The subjects in this study were all 5th grade students of MI Dipanegara Klirong Buluspesantren with a total of 28 students consisting of 16 male students and 12 female students. The instruments used in the study were observation sheets and item descriptions. Based on the results of the research, it can be revealed that there is an increase in students' understanding, if in the pre-cycle the average score of students only got a score of 65.32, but after taking action in the first cycle the students experienced an increase in the average grade of 72.12. While in the second cycle has an average of 83.91 with the percentage increase from pre-cycle to cycle I increased by 45.8%, while from cycle I to cycle II it increased by 4.28% and from pre-cycle to cycle II increased by 50 ,08%. Thus learning through the edutainment method can improve students' understanding of SKI learning Materials Kluafaur Rashidin: Uthman bin Affan in class 5 MI Dipanegara Ranterejo Klirong Kebumen.This research is motivated by the low understanding of students in the SKI subject matter of Khulafaur Rashidin Uthman bin Affan. From this problem, the researcher provides a solution by applying the edutainment learning method, which is a learning method by means of learning that is designed in such a way, so that the content of education and entertainment can be combined. The method in this research is classroom action research which is a research model that consists of four stages starting from planning, action, observation, and reflection. In this classroom action research, the researcher refers to the research scheme proposed by Kemmis and Tegart. The subjects in this study were all 5th grade students of MI Dipanegara Klirong Buluspesantren with a total of 28 students consisting of 16 male students and 12 female students. The instruments used in the study were observation sheets and item descriptions. Based on the results of the research, it can be revealed that there is an increase in students' understanding, if in the pre-cycle the average score of students only got a score of 65.32, but after taking action in the first cycle the students experienced an increase in the average grade of 72.12. While in the second cycle has an average of 83.91 with the percentage increase from pre-cycle to cycle I increased by 45.8%, while from cycle I to cycle II it increased by 4.28% and from pre-cycle to cycle II increased by 50 ,08%. Thus learning through the edutainment method can improve students' understanding of SKI learning Materials Kluafaur Rashidin: Uthman bin Affan in class 5 MI Dipanegara Ranterejo Klirong Kebumen.